1994
DOI: 10.1017/s0033291700029020
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial predictors of vulnerability to distress in the year following heart transplantation

Abstract: SynopsisThis study examines psychological symptomatology in a cohort of 72 heart transplant recipients followed longitudinally during their first year post-transplant. In keeping with research on other domains of life stressors and illnesses, a central study goal was to identify pre-transplant and perioperative psychosocial factors associated with increased vulnerability to, and maintenance of, elevated psychological distress levels post-transplant. Average anxiety and depression levels, but not anger–hostilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
55
0
3

Year Published

1999
1999
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(60 citation statements)
references
References 42 publications
2
55
0
3
Order By: Relevance
“…Previous researchers have shown similar findings. Dew and colleagues 1 found that anxiety and depression levels rise in the early post-transplant period but rapidly decrease over time in 67% of the patients. In a more recent study, Dew et al 4 documented poor psychologic adjustment to heart transplantation as a major contributor to reduced QOL and increased physical morbidity beyond the first 12 to 18 months after transplantation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous researchers have shown similar findings. Dew and colleagues 1 found that anxiety and depression levels rise in the early post-transplant period but rapidly decrease over time in 67% of the patients. In a more recent study, Dew et al 4 documented poor psychologic adjustment to heart transplantation as a major contributor to reduced QOL and increased physical morbidity beyond the first 12 to 18 months after transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…results in increased distress and anxiety, [1][2][3][4] and a number of patients find themselves confronted with the difficult and unexpected task of adapting to a chronic physical condition after the surgery. 5 For this reason, care of the heart transplant patient has evolved from focusing solely on survival to improving emotional well-being and quality of life (QOL).…”
mentioning
confidence: 99%
“…Likewise, studies on the effect of OHT on functional and psychologic outcomes show that, overall, OHT recipients report dramatic improvements in functional outcomes but continue to report psychologic distress several years after OHT surgery. 4,5 More recently, investigators 6,7 have judiciously examined factors associated with psychologic distress and disorders among OHT survivors that have led to a better understanding of OHT survivorship. However, few investigators have examined factors associated with fatigue among OHT recipients after surgery.…”
mentioning
confidence: 99%
“…[1][2][3][4] persons who undergo heart transplant experience increased psychological distress related both to postoperative physiological changes and to adjustment to a posttransplant treatment regimen fraught with side effects. 5 Recently, researchers have suggested that the need to cope with the physical loss of a heart and acceptance of a donor heart may be antecedent to feelings of psychological distress.…”
mentioning
confidence: 99%